Semantics of Mongolian words found in the work “Shezhire-i terakime” - Kenzhalin, Қ.К.; Baltabay, Д.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The study of the lexical layer of historical works and poems in the linguistic aspect plays an important role in determining the history of the formation and development of a language. Taking into account this significance, the work of Abulgazy Bahadur Khan “Shezhire-i terakime”, written in the 17th century, was considered as the object of study. During the study, Mongolian elements were analyzed from a comparative historical point of view, semantic commonalities and differences between the Turkic and Mongolian languages were identified. In addition to Turkic and Mongolian elements, Arabic and Persian words are found in its lexical layer. In historical linguistics, scientific views related to the historical formation and the penetration of Mongolisms into the Turkic languages are still being considered at a hypothetical level. The research article also conducts a lexical-semantic analysis of the words shyrai, daruga, kurultai, sheshen in the work “Shezhire-i terakime”. The usage of the analyzed words in a figurative or literal sense, phonetic, morphological features of the Turkic and Mongolian languages are studied. In order to increase the scientific significance of the article, examples from aphorisms, proverbs and sayings in the Turkic and Mongolian languages are given. In determining the etymology of Mongolian elements, scientific and theoretical conclusions and opinions of Altaic scientists and Turkologists are analyzed. Semantic, etymological analysis of linguistic units found in the work “Shezhire-i Terakime” serves as the basis for determining the historical continuity between the written Chagatai language and the Kazakh language.